Canada : Financial Sector Assessment Program-IOSCO Objectives and Principles of Securities Regulation-Detailed Assessment of Implementation. (IMF Staff Country Reports; Country Report ;, 2014)
This paper presents an assessment IMF report on implementation of the International Organization of Securities Commission (IOSCO) principles in Canada. It highlights that developing an integrated and robust view of risks to support supervisory actions remains a key challenge. The IMF report suggests that the securities regulators should continue to take steps to ensure timely decision making in policy formulation. However, the current governance arrangements, based on a consensus building approach across several entities, is expected to affect timeliness of decision making.